2021
DOI: 10.1155/2021/9999847
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Doxycycline on Survival in Abdominal Aortic Aneurysms in a Mouse Model

Abstract: Background. Currently, there is no reliable nonsurgical treatment for abdominal aortic aneurysm (AAA). This study, therefore, investigates if doxycycline reduces AAA growth and the number of rupture-related deaths in a murine ApoE−/− model of AAA and whether gadofosveset trisodium-based MRI differs between animals with and without doxycycline treatment. Methods. Nine ApoE−/− mice were implanted with osmotic minipumps continuously releasing angiotensin II and treated with doxycycline (30 mg/kg/d) in parallel. A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…[ 34 ] Unfortunately, its effects on endothelial remodeling in vitro did not translate to in vivo through systemic administration. [ 35 ] On the other hand, local use could mimic the in vitro observations of previous reports. [ 36 ] Here, we showed that STB gels loaded with DOX have ablative properties ( Figure ) as well as MMP inhibitory effects (Figure 4) and showed endothelial modulation (Figure 6).…”
Section: Resultsmentioning
confidence: 82%
“…[ 34 ] Unfortunately, its effects on endothelial remodeling in vitro did not translate to in vivo through systemic administration. [ 35 ] On the other hand, local use could mimic the in vitro observations of previous reports. [ 36 ] Here, we showed that STB gels loaded with DOX have ablative properties ( Figure ) as well as MMP inhibitory effects (Figure 4) and showed endothelial modulation (Figure 6).…”
Section: Resultsmentioning
confidence: 82%
“…Without timely treatment, the mortality of ruptured AAA is extremely high [9]. However, unexpectable complications after surgery, high in-hospital mortality of ruptured AAA, and controversial clinical strategies for small unruptured AAA all remind us that it's urgent to explore associated mechanisms of AAA progression and screen effective strategies for AAA treatment [10][11][12]. Phytochemicals, also known as secondary plant metabolites [13], are bioactive plant-derived chemical constituents [14].…”
Section: Introductionmentioning
confidence: 99%